2020
DOI: 10.21203/rs.3.rs-96813/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Multi-Center Retrospective Study of Clinical features, Laboratory Characteristics, and Outcomes of 325  Hospitalized Children with Coronavirus Disease 2019 (COVID-19); A Preliminary Report from Iranian Network for Research in Viral Diseases (INRVD)

Abstract: Background: The objectives of this study were to analyze the clinical features and laboratory profiles and risk factors associated with critical illness of children with SARS-CoV-2.Methods: 325 COVID-19 pediatric patients were recruited through a collaborative research network between March and May 2020. Demographics, clinical, laboratory, and radiological results were obtained from patient files. Results: Of 325 patients, 189 (58%) and 136 (42%) were males and females, respectively. The mean age was 6.18 ± 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…Still, one study suggests that strategies addressing family worry, obtaining job-related income support, and helping families get tangible resources may positively affect family psychological health (9). in previous studies of children with COVID-19 who were hospitalized in Iran, the average age was six years, 58 percent were boys, and the frequency of distribution of age and sex was almost similar to this study (10).…”
Section: Discussionsupporting
confidence: 80%
“…Still, one study suggests that strategies addressing family worry, obtaining job-related income support, and helping families get tangible resources may positively affect family psychological health (9). in previous studies of children with COVID-19 who were hospitalized in Iran, the average age was six years, 58 percent were boys, and the frequency of distribution of age and sex was almost similar to this study (10).…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have reported rates of CXR abnormalities of 33 to 54%, 8 18 compared with 15% in our study. In a previous Turkish pediatric study, Böncüoğlu et al found that abnormal CT findings correlated with elevated CRP levels.…”
Section: Discussionsupporting
confidence: 50%
“…8 9 11 12 13 14 15 As in our study, the most common symptoms are usually reported to be fever and cough. 8 9 11 12 13 14 15 16 17 18 However, in a UK study of 1,734 children, the most common symptoms were headache (62%) and fatigue (55%). 19 SARS-CoV-2 infections in children have different paths and are less severe than in adults in terms of clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 virus (Severe Acute Respiratory Syndrome Coronavirus 2), causing the disease called COVID-19, has led to the death of over a million people globally. The COVID-19 outbreak forced governments to introduce severe restrictions and limitations that have negatively influenced many areas of the economy, including the sports sector [ 9 , 10 , 11 ], and brought about obstacles to outdoor physical activity [ 12 , 13 ]. As long-lasting lower physical activity is harmful to health and physical fitness, some researchers provide recommendations to exercise at home to maintain, at least in part, the previous level of physical capacity [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%